Sprache in Interaktion : Analysemethoden und Untersuchungsfelder. - Imo, Wolfgang (Linguistik, Impulse & Tendenzen., 2013)
While linguistics traditionally focused on a language use oriented towards the written norm, this bookemphasizes the interactional use of language. On a theoretical and empirical basis, the author develops linguistic concepts to analyzeboth spoken and written interactional language. Byillustrating the relevance of syntactic structures of interactional language, the book also contributes to areas of applied linguistics, such as grammar writing and German as a second language.